Resilience of Loin Meat Microbiota and of Resistance Genes to a Chlortetracycline Treatment in Weaned Piglets - Xavier C. Monger; Linda Saucier; Alex-An Gilbert; Sophie Gosselin; Éric Pouliot; Sylvain Fournaise; Antony T. Vincent (MDPI AG, 2024)
Objectives: This project studied the impact of a chlortetracycline treatment in weaning piglets on the taxonomy and antibiotic resistance gene (ARG) content of the microbiomes on carcasses and loins. Methods: Two groups of piglets from two farrowing barns with either an average or a lower sanitary health status were used. Each group was divided in half: a control group and a treatment group receiving feed supplemented with 660 g of chlortetracycline per tonne for 21 days. The piglets then went through fattening and were sent to the abattoir when they reached the targeted slaughter weight. Results: The microbiomes of the pig carcasses and loins were sampled, and DNA was extracted and sequenced with a whole-genome approach. The microbiomes of the carcasses differed depending on the farrowing barn source in both taxonomical composition and ARG content; however, the microbiomes on the loins were similar, regardless of the farrowing barn source and the treatment group. Conclusions: While there were differences in the carcass microbiomes between treatments after processing by the abattoir, the loin microbiomes were consistent and unaffected by treatment with chlortetracycline or the sanitary status of the farrowing barn.